Novel Approaches of Public Policy Interventions for Valuating and Harnessing Data from the Digital Health Metaverse to Enhance Health Management Through Emerging Technologies - Reddy Chedabavi, Chandrashekhar (Digital Repository of Theses - SSBM Geneva, 2025)
The implementation of health policies plays a crucial and critical role in the healthcare industry, as it involves the process of transforming policy objectives into practical measures and achieving the desired results. In the context of India, it is evident that despite the implementation of several health and technology policies, there continue to exist substantial deficiencies in both their efficient development and implementation. However, the advent of the digital health metaverse presents new opportunities for transforming healthcare delivery. This metaverse incorporates several technologies such as Digital Twins, Augmented Reality (AI), Artificial Intelligence (AI), Virtual Reality (VR) and Machine Learning(ML). This research proposal presents a thorough study that seeks to examine the criteria that contribute as a gap in the implementation of health and technology policies in India. Additionally, it explores novel strategies that utilize the future potential and value of the digital health metaverse in addressing these gaps in policy formulation and implementation. The legislative bodies of the Indian parliament have enacted rules and regulations to manage the health ecosystem in India, so establishing the authority of the Indian government in this domain. Several Indian acts and laws are in place, such as the Consumer Protection Act of 2019, the Surrogacy Bill of 2018, the Mental Health Act of 1987, the Pharmacy Act of 1948, the Biomedical Waste Management and Handling Rules of 1998, Drug and Cosmetics Act of the year 1940 and new Digital Personal Data Protection Act 2023, among others. Several approaches will be applied to evaluate the shortcomings in the studies. These comprise the review of the research design and methodology, the application of data collecting techniques including systematic reviews, qualitative interviews, and surveys, the development of selection criteria for inclusion of the literature, and the use of both quantitative and qualitative data analysis approaches. The study's research covers a wide spectrum of subjects and produces several results: A. The present discourse aims to explicate the definition and conceptual framework of health policy implementation. B. Overview of the Health Policy Landscape in India The present study focuses on the intervention and analysis of health policy gaps in India, specifically in relation to the advancements in technology. 1. The policy-practice gap denotes the divergence between the development and execution of policies in a certain setting. 2. Challenges in Institutional Capacity, Governance, and Coordination 3. Identifying and Addressing Policy Gaps to Enhance Benefits for Key Stakeholders 4. The evolution, adoption, and restrictions of technology. 5. Deficiencies in Monitoring and Evaluation 6. The concept of political will and stakeholder engagement is of great significance in the field of politics and governance. “Political will” refers to the determination and political leaders commitment to prioritize and address certain issues or challenges. It involves the allocation of resources, implementation of policies, and the mobilization of support. Past research has lacked a comprehensive and systematic strategy in the management of restrictions, as well as unique methodologies for monitoring the digital health metaverse. The efficacy of health initiatives in India is impeded by many gaps and obstacles. This study emphasizes the significance of reducing the gap between policy and its practice. It underscores the importance of enhancing the capacity of institutions, improving governance and coordination, addressing limitations in resources, strengthening monitoring and evaluation mechanisms, taking into account socio-cultural factors, and fostering political will and engagement of stakeholders. These steps are crucial for the effective implementation of policies. By effectively tackling these aforementioned difficulties, India has a potential to improve the execution of health policy, hence resulting in improved healthcare results for its population.